Respostas
respondido por:
23
{x - 3y = 9
{2x + 3y = 6
3x = 15 x - 3y = 9
x = 15/3 5 - 3y = 9
x = 5 -3y = 9 - 5
-3y = 4
y = 4/-3
y = -4/3
S={(5,-4/3)}
{2x + 3y = 6
3x = 15 x - 3y = 9
x = 15/3 5 - 3y = 9
x = 5 -3y = 9 - 5
-3y = 4
y = 4/-3
y = -4/3
S={(5,-4/3)}
respondido por:
4
Resposta:
{x - 3y = 9
{2x + 3y = 6
3x = 15 x - 3y = 9
x = 15/3 5 - 3y = 9
x = 5 -3y = 9 - 5
-3y = 4
y = 4/-3
y = -4/3
S={(5,-4/3)}
Explicação passo-a-passo:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás